SLC3A2/CD98hc, autophagy and tumor radioresistance: a link confirmed - Digomann, David; Linge, Annett; Dubrovska, Anna (Autophagy, 2019)
SLC3A2/CD98hc (solute carrier family 3 member 2) and its light chain subunits constitute the heterodimeric transmembrane complexes that mediate amino acid transport and regulate MTOR and macroautophagy/autophagy. Despite the proven tumorigenic role of SLC3A2 in a number of cancers including head and neck squamous cell carcinomas (HNSCC), the link between SLC3A2, autophagy regulation and tumor radioresistance remained elusive. In a recently published study we demonstrated that low levels of SLC3A2 and SLC7A5/LAT1 protein expression significantly correlate with good clinical prognosis in locally advanced HNSCC treated with primary radiochemotherapy. The SLC3A2-deficient HNSCC cells show a higher radiosensitivity and increased autophagy levels. We found that autophagy activation is a tumor survival strategy to overcome nutrient stress by lack of SLC3A2 and to withstand radiation-mediated cell damage. Inhibition of the autophagy activation in SLC3A2 knockout HNSCC cells by knockdown of ATG5 expression or treatment with bafilomycin A1 results in radiosensitivity. Consequently, the expression levels of ATG5 correlates with overall survival in HNSCC patients, and autophagy inhibition in combination with SLC3A2-targeted therapy can be a promising strategy for HNSCC radiosensitization.Abbreviations: CD98hc: CD98 heavy chain CSC cancer stem cells; EAA: essential amino acids; GSH: glutathione; MTOR: mammalian target of rapamycin; HNSCC: head and neck squamous cell carcinoma; RCTx: primary radiochemotherapy; PORT-C: postoperative radiochemotherapy; ROS: reactive oxygen species; SLC3A2: solute carrier family 3 member 2; TCA cycle: tricarboxylic acid cycle.
Gesehen am 19.03.2020